Age-specific incidence, treatment, and survival trends in esophageal cancer: a Dutch population-based cohort study. (4th May 2022) - Al-Kaabi, Ali; Baranov, Nikolaj S.; van der Post, Rachel S.; Schoon, Erik J.; Rosman, Camiel; van Laarhoven, Hanneke W. M.; Verheij, Marcel; Verhoeven, Rob H. A.; Siersema, Peter D.
Abstract: Background: Data on the age-specific incidence of esophageal cancer are lacking. Our aim was to investigate the age-stratified incidence, treatment, and survival trends of esophageal cancer in the Netherlands, with a focus on adults <50 years. Material and methods: Patients diagnosed with esophageal cancer were included from the nationwide Netherlands Cancer Registry (1989–2018). Follow-up data were available until 31 December 2018. Annual percentage changes of incidence were analyzed according to age group (<50, 50–74, and ≥75 years) and histology type: adenocarcinoma (EAC) and squamous cell carcinoma (ESCC). Treatment trends and relative survival rates (RSR) were estimated by age and stage grouping. Results: A total 59, 584 patients were included. In adults <50 years, EAC incidence tripled (mean increase per year: males 1.5%, females 3%), while the incidence of ESCC decreased (mean decrease per year: males −5.3%, females −4.3%). Patients <50 years more often presented with advanced disease stages compared to older patients and were more likely to receive multimodality treatments. Most patients <50 years with potentially curable disease were treated with neoadjuvant chemoradiotherapy followed by surgery compared to patients 50–74 and ≥75 years (74% vs. 55% vs. 15%, respectively; p < .001), and received more frequent systemic therapy once staged with palliative disease (72% vs. 54% vs. 19%, respectively; p < .001). The largest RSR improvement was seen in patients <50 years with early-stage (five years: +47%), potentially curable (five years: +22%), and palliative disease (one year: +11%). Over time, a trend of increasing survival difference was seen between patients <50 and ≥75 years with potentially curable (five-year difference: 17% to 27%) and palliative disease (one-year difference: 11% to 20%). Conclusion: The incidence of EAC is increasing in adults <50 years in the Netherlands. Differences in the use of multimodality treatments with curative or life-prolonging intent in different age categories may account for increasing survival gaps.